2019 IEEE 8th International Workshop on Computational Advances in Multi-Sensor Adaptive Processing (CAMSAP) 2019
DOI: 10.1109/camsap45676.2019.9022612
|View full text |Cite
|
Sign up to set email alerts
|

Gaussian Mixture Models for Stochastic Block Models with Non-Vanishing Noise

Abstract: Community detection tasks have received a lot of attention across statistics, machine learning, and information theory with a large body of work concentrating on theoretical guarantees for the stochastic block model. One line of recent work has focused on modeling the spectral embedding of a network using Gaussian mixture models (GMMs) in scaling regimes where the ability to detect community memberships improves with the size of the network. However, these regimes are not very realistic. This paper provides tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…In this setting, we found that the BP has convergence issues and so we compare our theoretical results with the empirical performance of a spectral method [33] applied to a linear combination of the adjacency matrices. Specifically, we obtain estimates of the community labels using the following procedure.…”
Section: Correlated Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…In this setting, we found that the BP has convergence issues and so we compare our theoretical results with the empirical performance of a spectral method [33] applied to a linear combination of the adjacency matrices. Specifically, we obtain estimates of the community labels using the following procedure.…”
Section: Correlated Networkmentioning
confidence: 99%
“…Next, we retain the eigenvectors associated with the second and third leading eigenvalues in the spectral decomposition ofG. The relationship between these eigenvectors and the node labels is characterized using a Gaussian mixture model (GMM) approach described in [33], evaluated withR. Figure 2 shows the MSE as a function of the SBM parameter r. The solid blue line corresponds to the trace of the heuristic upper bound to the MMSE for two correlated networks computed from Theorem 2, and the red line corresponds to the upper bound for a single network.…”
Section: Correlated Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Spectral methods leverage an embedding of the adjacency matrix in a Euclidean space and then estimate communities by clustering in the embedded space. There are many variations on spectral methods (Rohe et al, 2011;Binkiewicz et al, 2017b;Abbe, 2018;Mathews et al, 2019;Suwan et al, 2016), but here we concentrate on a normalized graph Laplacian embedding. Specifically, let ).…”
Section: Initializing Umentioning
confidence: 99%
“…Noisy label problem have been investigated for a long time in the machine learning literature and label noise-robust algorithms have numerous applications in medical image processing, spam filtering [1,2,3], Alzheimer disease prediction [1], gene expression classification [4] , text processing [5,6,7,8,9,10,11], image recognition [12,13,14,15,16,17]. Noisy labels are introduced by expert error and other unknown and unexpected factors.…”
Section: Introductionmentioning
confidence: 99%